Gaza in crisis : reflections on Israel's war against the Palestinians. - Pappé, Ilan (Haymarket Books, 2013)
As Israel continues its barbaric assault on Gaza, Noam Chomsky and Ilan Pappe put the recent campaign against Gaza.